ANALISIS PENGARUH KUALITAS LAYANAN DAN NILAI YANG DIRASAKAN TERHADAP KEPUASAN PELANGGAN BRT TRANS SEMARANG - Putri, Sri Wiryani; Kusumawardhani, Amie (Diponegoro Journal of Management, 2015)
Implementation of mass transportation is good and decent for the community to deal with theproblem of urban transportation is by giving good service as the service more secure, convenient reliable, fast, and efficient. This study aimed to analyze whether the service quality and perceived value effect on passenger satisfaction BRT Trans Semarang.The sample in this study were 122 respondents had used BRT Trans Semarang service more than twice. The analytical method used is the analysis of Structural Equation Modeling(SEM).The results of SEM analysis showed that the service quality has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on perceived value, perceived value has a positive and significant effect on customer satisfaction.Service quality and perceived value need to be improved to increase passenger satisfactionBRT Trans Semarang.